Literasi Fintech Bagi Start-Up Mahasiswa di Malaysia - Dwi Eko Waluyo; Usman Usman; Kamila Nasywa Putri; Ukhti Maylita Haryani; Wijayanti Wijayanti; Devi Wahyuni (Pusat Riset dan Inovasi Nasional, 2025)
The goal of this activity is to improve students' understanding of the advantages of fintech for business startups. Fintech plays an important role in expanding financial access and increasing transaction efficiency. It can help students manage and develop their businesses more easily, particularly through digital payment processes. The program was implemented through socialization and workshops for students who use fintech services. The results showed an increase in fintech literacy, which impacted the optimal utilization of fintech products. Recommendations were made for students to maximize their use of fintech and for fintech startups to develop products that suit the needs of aspiring student entrepreneurs.